Alterations of selenium level and speciation during milling and cooking in different wheat cultivars. (12th January 2023) - Xu, Sinan; Wang, Han; Wang, Yanan; Zhou, Xianghan; Yao, Yaya; Zhang, Lijing; Li, Huijing; Pei, Jiawei
Abstract: BACKGROUND: Selenium (Se) deficiency is a recognized problem that threatens the health of people worldwide, and wheat is grown worldwide and is one of the major sources of dietary Se. Since there are few studies that have investigated the changes in Se content and speciation of different varieties of Se‐enriched wheat from primary to deep processing, we studied four naturally Se‐enriched kinds of wheat and two Se‐fertilized kinds of wheat. RESULTS: Glutenin‑ and albumin‐bound Se accounted for the highest proportion of protein‐bound Se in refined wheat flour (7.29 ± 0.19 to 10.82 ± 0.50% and 6.16 ± 0.34 to 8.45 ± 0.07%); water‐soluble polysaccharide‐bound Se accounted for the highest proportion of polysaccharide‐bound Se in refined wheat flour (12.02 ± 0.54 to 24.62 ± 1.87%). Coarse bran Se content was significantly higher than refined wheat flour (137.94 ± 7.80 to 174.55 ± 5.09% for unpeeled wheat, 147.27 ± 10.96 to 187.72 ± 17.70% for peeled wheat). The peeling and processing of wheat into flour had different effects on Se the content and speciation dependent on the particular wheat variety. Whole wheat flour enabled better retention of selenomethionine (101.64 ± 2.32 to 138.41 ± 2.84% for unpeeled wheat, 158.59 ± 13.72 to 250.20 ± 4.94% for peeled wheat). The cooking process had no significant effect on Se content, but Se species were possibly interconverted. CONCLUSION: The organic Se content of different varieties of Se‐enriched wheat was different, but the milling and cooking process retained the total Se and Se speciation better, which could be used for daily Se supplementation for Se‐deficient people. © 2022 Society of Chemical Industry.